2012
DOI: 10.1111/j.1365-2524.2012.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Supporting African refugees in Canada: insights from a support intervention

Abstract: Although evidence suggests the importance of social support for refugees, this knowledge has not been invoked to systematically develop culturally congruent support interventions that help refugees adapt to life in receiving countries. The objective of this study was to design and pilot test a culturally congruent intervention that meets the support needs and preferences of two ethno-culturally distinct refugee groups. Support was delivered to Somali and Sudanese refugees (n = 58), by trained peer and professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
121
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(131 citation statements)
references
References 34 publications
(37 reference statements)
6
121
0
4
Order By: Relevance
“…Transition to parenthood in a new country places refugee parents at increased risk for adverse mental health outcomes. Recent reports call for more attention to culturespecific and intra-cultural variations in refugee stress, acculturation, and mental health outcomes of migration [60,61]. The qualitative data supplemented and elaborated the data elicited through standardized quantitative measures.…”
Section: Discussionmentioning
confidence: 99%
“…Transition to parenthood in a new country places refugee parents at increased risk for adverse mental health outcomes. Recent reports call for more attention to culturespecific and intra-cultural variations in refugee stress, acculturation, and mental health outcomes of migration [60,61]. The qualitative data supplemented and elaborated the data elicited through standardized quantitative measures.…”
Section: Discussionmentioning
confidence: 99%
“…Peer models have been used successfully in immigrant/refugee acculturation programs throughout the world including peer education programs for communicable illnesses (Broadhead et al, 2002;Thomas, Clarke, & Kroliczak, 2008); whereas support groups have been efficacious in treating numerous populations ranging from addiction to new parent support groups (Yalom, 2005). Research suggests that after social support interventions, refugees reported increased social integration, decreased loneliness, and healthier coping skills (Stewart, Simich, Shizha, Makumbe, & Makwarimba, 2012). A strengths-based support group model embraces concepts like cultural humility and competence as it is rooted in community growth and strength.…”
Section: Group Work With Refugeesmentioning
confidence: 99%
“…"Fear of police and other authorities is a major barrier" to developing social links with government, because of their previous persecution and torture experiences [61].Other barriers that hindered refugees from widening their social capital and networks also include gender inequities led to the differences in the content and structure of social network between male and female refugees [43]; inadequate information and access to services limited the opportunities for refugees to reach out and be connected [61,63,65]; family conflicts resulted from refugees experiencing all the pre-migration, migration, and post-migration stress and traumas, led to the fragile kinships [56,66]; low self-esteem led to the hesitation to communicate [60]; Shame of asking for help led to the isolation and loneliness [36]. Throughout the years, both researchers and practitioners have been proposing different solutions including conducting support interventions, to enhance refugees' social integration in their host countries [24,33,60,64,67,68]. Recommendations were made, including (1) provide refugees with more training programs for them to learn their host country's languages, cultures and customs, professional skills, and legal and healthcare systems [24,33,68]; (2) provide more programs to facilitate mutual understanding and respect and reduce racial and cultural tensions between refugee communities and host communities [64]; (3) provide refugees with more accessible access to updated and reliable information, and social and healthcare services [24,33,64,68]; (4) facilitate speedy and easier family unification for refugees who have family members outside their host countries [24,33]; [5] recognize refugees' skills and abilities they bring to their host countries and promote their self-efficacy and independency [24,68]; [6] improve the awareness of refugees' culture among the general public in host countries prior to refugees' arrivals…”
Section: Discussionmentioning
confidence: 99%